2020
DOI: 10.21203/rs.3.rs-35251/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Selection and validation of reference genes for measuring gene expression in Toona ciliata under different experimental conditions by quantitative real-time PCR analysis

Abstract: Background: Before studying gene expression of different organisms, it is important to determine the best reference gene. At present, the most accurate method of detecting gene expression is quantitative real-time PCR (RT-qPCR). With this method, reference genes that are stable in different biological systems and under different conditions can be obtained. Toona ciliata Roem (T. ciliata). is a valuable and fast-growing timber specie. In this study, 20 reference genes were identified using RT-qPCR, as a primary… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…The expression of an "ideal" reference gene will not vary with treatment or physiological state in the tissue studied. However, several studies have shown that no perfect reference gene exists because the reference gene can be influenced by species, different tissues, developmental stages and diseases, etc [2,17,29]. Consequently, it is becoming an essential component of qPCR to systematically evaluate common and novel reference genes derived from genomewide analyses so as to improve the reliability of research results.…”
Section: Introductionmentioning
confidence: 99%
“…The expression of an "ideal" reference gene will not vary with treatment or physiological state in the tissue studied. However, several studies have shown that no perfect reference gene exists because the reference gene can be influenced by species, different tissues, developmental stages and diseases, etc [2,17,29]. Consequently, it is becoming an essential component of qPCR to systematically evaluate common and novel reference genes derived from genomewide analyses so as to improve the reliability of research results.…”
Section: Introductionmentioning
confidence: 99%